Modified resin material for ski helmet goggles and preparation method thereof
By adding modified mesoporous silica to the modified resin material for ski helmet goggles, adjusting the light transmittance of the paint and grafting hydrophilic and hydrophobic groups, the problem of short-lasting anti-fog coating effect of existing anti-fog coating is solved, and the long-term anti-fog and friction resistance of ski goggles is achieved.
Patent Information
- Application Number
- CN202411964127.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Due to its hydrophilic characteristics, the existing anti-fog coating is easily soluble in water, resulting in a short anti-fog maintenance time and is prone to failure in long-term use in outdoor environments.
By adding modified mesoporous silica to the modified resin material for ski helmet goggles, the light transmittance of the paint is adjusted and hydrophilic and hydrophobic groups are grafted, the hydrophilic-oleophobic properties of the paint is achieved, thereby improving anti-fog performance and durability.
It realizes the long-term anti-fog effect of ski goggles, enhances the friction resistance and self-cleaning performance of the paint, and ensures the long-lasting anti-fog performance of the goggles in outdoor environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic materials, and in particular to a modified resin material for ski helmet goggles and a preparation method thereof. Background Art
[0002] Ski goggles are essential eye protection equipment for skiing. They directly affect the skier's vision, which determines the skier's safety. Snow has a strong reflective effect on sunlight, and the cold wind during skiing is also very irritating to the eyes. Ski goggles can not only protect the eyes, but also provide functions such as UV protection, anti-glare, and anti-fogging, providing a clear field of vision and protecting the eyes from external damage. In order to protect the eyes, ski goggles are often more airtight. Atomization is the process of water changing from vapor phase to liquid phase. When humid air contacts a solid that is less than or equal to its dew point, it condenses into small and dispersed droplets on the solid surface, and atomization occurs on the solid surface. During skiing, due to the high temperature inside the goggles and the difficulty of water dissipating quickly, the formation of fog on the lens will go through the stages of droplet growth and droplet nucleation. When the droplet nucleation tends to form independent droplets, the small water droplets formed by condensation adhere to the inner wall. When the contact angle of the droplets is greater than 48.8°, due to the existence of total reflection of the outer circle, the outer circle of the droplets is a low-light-transmittance area and the inner circle is a high-light-transmittance area. The difference in light transmittance causes the lens to become blurred, affecting its normal work.
[0003] For the anti-fog treatment of lens substrates, the existing technology generally adopts an external coating method to deposit an anti-fog coating on the surface of the substrate to adjust the affinity between the lens substrate and water droplets; the anti-fog coating can be divided into an organic anti-fog coating and an inorganic anti-fog coating; among them, the main effective ingredients of the organic anti-fog coating are some polymers containing hydrophilic functional groups. The polymers prepared from these hydrophilic hydroxyl, carboxyl, sulfonic acid or dihydrogen phosphate monomers have good processability, high transparency and other characteristics in addition to being hydrophilic, and are ideal raw materials for anti-fog coatings. However, due to the inherent hydrophilic characteristics of this type of coating, it is easily soluble in water, resulting in a short anti-fog effect of the coating, and it is easy to fail in long-term use in outdoor environments. In addition, due to the use of the anti-fog coating, a water film is easily formed on the surface of the lens. The water film effectively improves the material's adsorption of hydrocarbons in the air, greatly increases the occurrence of the lens being contaminated by hydrocarbons in the air, affects the formation of a continuous water film on the lens surface, and causes the lens to achieve long-term anti-fog. Summary of the invention
[0004] The purpose of the present invention is to provide a modified resin material for ski helmet goggles and a preparation method thereof, so as to solve the following technical problems: The existing anti-fog coating is a hydrophilic coating, which is easily soluble in water, resulting in a short anti-fog duration of the coating and easy failure in long-term use in outdoor environments.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a modified resin material for ski helmet goggles comprises the following steps: A1: In a nitrogen atmosphere, acrylate monomer, modified mesoporous silica, azobisisobutyronitrile and methanol are added to a reaction kettle and dispersed evenly. The temperature is controlled at 60-70°C, and the reaction is kept warm for 18-24 hours. Toluene is added to terminate the reaction and dried to obtain a silica-modified acrylate resin. A2: According to the raw material ratio, the silica-modified acrylic resin, the reactive diluent, the photoinitiator, the leveling agent and the solvent are blended to obtain a modified resin material; The preparation method of modified mesoporous silica comprises the following steps: S1: Add epoxidized mesoporous silica and N,N-dimethylformamide to a reaction kettle and disperse them evenly, add 2-acrylamide-2-methylpropanesulfonic acid and hydroquinone, control the temperature at 65-75°C, keep the reaction warm for 3-6 hours, add 50-60°C deionized water to stop the reaction, filter, wash and dry to obtain component 1; hydroquinone is used as a free radical inhibitor to effectively avoid high-temperature polymerization of the acrylamide group of 2-acrylamide-2-methylpropanesulfonic acid; S2: In a nitrogen atmosphere, component 1, 1,1,2,2-tetrahydroperfluorohexyl iodide, sodium bicarbonate, sodium dithionite, and acetonitrile are added to a reaction kettle and dispersed evenly, deionized water is added, the temperature is raised to 40-50°C, the temperature is kept for reaction for 6-9 hours, and then washed and dried to obtain component 2; S3: In a nitrogen atmosphere, component 2, lithium aluminum hydride and tetrahydrofuran are added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 6-9 hours, deionized water is added, filtered, washed and dried to obtain component 3; S4: In a nitrogen atmosphere, add triethylamine, tetrahydrofuran into a reaction kettle and disperse evenly, add acryloyl chloride, react at room temperature for 3-6 hours, adjust the pH value to 7-8, filter, wash and dry to obtain modified mesoporous silica.
[0006] As a further solution of the present invention: the acrylate monomer is obtained by mixing methyl methacrylate, butyl methacrylate and hydroxyethyl acrylate in a molar ratio of 1:1-2:2-3; the addition ratio of the acrylate monomer, modified mesoporous silica, azobisisobutyronitrile and methanol in A1 is 50-80g: 5-15g: 1.5-2: 400-1000mL.
[0007] As a further embodiment of the present invention: the modified resin material in A2 comprises the following raw materials in parts by weight: 50-80 parts of silica-modified acrylate resin, 5-10 parts of reactive diluent, 5-6 parts of photoinitiator, 0.1-2 parts of leveling agent, 1-2 parts of auxiliary agent, and 40-60 parts of solvent; The active diluent is one or more of acrylic acid, methacrylic acid, and hydroxyethyl methacrylate mixed in any ratio; The photoinitiator is a mixture of benzophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone in a mass ratio of 2:2-3; The leveling agent is any one of BYK-306, BYK-333, and BYK-3700; The solvent is either ethanol or isopropanol.
[0008] As a further scheme of the present invention: the preparation method of epoxidized mesoporous silica comprises the following steps: adding epichlorohydrin, potassium hydroxide and tetrabutylammonium sulfate into a reaction kettle and dispersing them evenly, adding mesoporous silica, stirring at room temperature for 12-24 hours, centrifuging, washing and drying to obtain epoxidized mesoporous silica.
[0009] As a further solution of the present invention: the addition ratio of epichlorohydrin, potassium hydroxide, tetrabutylammonium sulfate and mesoporous silica is 1-1.1 g: 0.6-1 g: 0.05-0.1 g: 10 g.
[0010] As a further solution of the present invention: the addition ratio of epoxidized mesoporous silica, N,N-dimethylformamide, 2-acrylamido-2-methylpropanesulfonic acid and hydroquinone in S1 is 10g: 50-100mL: 2-3g: 0.01-0.02g.
[0011] As a further scheme of the present invention: the addition ratio of component 1, 1,1,2,2-tetrahydroperfluorohexyl iodide, sodium bicarbonate, sodium dithionite, acetonitrile and deionized water in S2 is 10g:3.7-5.6g:0.8-1.2g:1.8-2.8g:50-100mL:25-50mL.
[0012] As a further solution of the present invention: the addition ratio of component 2, lithium aluminum hydride, tetrahydrofuran and deionized water in S3 is 10g: 1-2g: 50-100mL: 5-10mL.
[0013] As a further solution of the present invention: the addition ratio of components tris, triethylamine, tetrahydrofuran and acryloyl chloride in S4 is 10g:1-1.5g:50-100mL:0.3-0.6g.
[0014] A modified resin material for ski helmet goggles is made by any one of the above preparation methods.
[0015] Beneficial effects of the present invention: The present application uses tetrabutylammonium sulfate as a catalyst, and the ring-opening reaction of epichlorohydrin and the etherification reaction of the hydroxyl groups on the surface of the mesoporous silica are carried out, and the ring-closing reaction is carried out under the action of the strong base of potassium hydroxide to obtain epoxidized mesoporous silica. The present application first uses the epoxy group on the surface of the epoxidized mesoporous silica to undergo a ring-opening reaction with the sulfonic acid group of 2-acrylamide-2-methylpropanesulfonic acid to obtain component one; and uses the double bond on component one to undergo free radical addition with 1,1,2,2-tetrahydroperfluorohexyl iodide to obtain component two; then uses lithium aluminum hydride to reduce and deiodinate to obtain component three; finally, uses acryloyl chloride to react with the hydroxyl groups of component three to graft the double bond on the surface of silica to obtain modified mesoporous silica.
[0016] The present application uses silica-modified acrylate resin as the matrix of the modified resin material coating. The present application modifies mesoporous silica in the process of preparing the acrylate resin to obtain silica-modified acrylate resin. The mesoporous properties of the modified mesoporous silica itself effectively adjust the light transmittance of the coating, and the double bonds grafted on the molecular chains on the surface of the mesoporous silica effectively graft it onto the molecular chains of the acrylate resin substrate, effectively avoiding the problem of a short anti-fog duration of the coating due to its water solubility during use. The present application grafts hydrophilic groups near the surface of mesoporous silica and grafts hydrophobic groups on the surface away from the mesoporous silica, and adjusts the density of perfluorinated chains on the surface of the mesoporous silica to achieve the hydrophilic-oleophobic properties of the coating, and realizes the presence of defects of appropriate size in the outermost fluorinated layer of the coating to prepare a responsive surface, so that the fluorinated layer can prevent larger oil molecules from penetrating the coating, and can also allow smaller water molecules to rearrange the surface molecules through the fluorinated layer to reach the more hydrophilic hydrophilic layer to form a water film, thereby achieving an anti-fog effect; and the flow of water can also take away the oil droplets on the surface, thereby achieving a self-cleaning effect; the modified resin material prepared by the present application is used as a coating and applied to the surface of the lens of the goggles to obtain goggles with excellent and long-lasting anti-fog performance. Moreover, with the addition of the modified mesoporous silica prepared by the present application, the material is given excellent friction resistance and self-cleaning properties, giving the ski goggles the advantage of long-lasting anti-fog. DETAILED DESCRIPTION
[0017] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1 g of epichlorohydrin, 0.6 g of potassium hydroxide, and 0.05 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, stirred at room temperature for 12 h, centrifuged, washed, and dried to obtain epoxidized mesoporous silica; S3: 10 g of epoxidized mesoporous silica and 50 mL of N,N-dimethylformamide were added to a reaction kettle and dispersed evenly, 2 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.01 g of hydroquinone were added, the temperature was controlled at 65°C, the reaction was kept warm for 3 h, 50°C deionized water was added to stop the reaction, the reaction was filtered, washed and dried to obtain component 1; S4: In a nitrogen atmosphere, 10 g of component 1, 3.7 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 0.8 g of sodium bicarbonate, 1.8 g of sodium dithionite, and 25 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 40°C, the reaction was kept warm for 6 hours, and then washed and dried to obtain component 2; S5: In a nitrogen atmosphere, 10 g of component 2, 1 g of lithium aluminum hydride, and 50 mL of tetrahydrofuran were added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 6 h, 5 mL of deionized water was added, filtered, washed, and dried to obtain component 3; S6: In a nitrogen atmosphere, 10 g of component three, 1 g of triethylamine, and 50 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly, 0.3 g of acryloyl chloride was added, and the mixture was reacted at room temperature for 3 h. The pH value was adjusted to 7, and the mixture was filtered, washed, and dried to obtain modified mesoporous silica.
[0019] Example 2 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1 g of epichlorohydrin, 0.8 g of potassium hydroxide, and 0.08 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, stirred at room temperature for 18 h, centrifuged, washed, and dried to obtain epoxidized mesoporous silica; S3: 10 g of epoxidized mesoporous silica and 70 mL of N,N-dimethylformamide were added to a reaction kettle and dispersed evenly, 2.5 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.01 g of hydroquinone were added, the temperature was controlled at 70°C, the reaction was kept warm for 4.5 h, 55°C deionized water was added to stop the reaction, the reaction was filtered, washed and dried to obtain component 1; S4: In a nitrogen atmosphere, 10 g of component 1, 4.5 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 1 g of sodium bicarbonate, 2.5 g of sodium dithionite, and 40 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 45°C, the reaction was kept warm for 8 hours, and then washed and dried to obtain component 2; S5: In a nitrogen atmosphere, 10 g of component 2, 1.5 g of lithium aluminum hydride, and 70 mL of tetrahydrofuran were added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 8 h, 7 mL of deionized water was added, filtered, washed, and dried to obtain component 3; S6: In a nitrogen atmosphere, 10 g of component three, 1.2 g of triethylamine, and 70 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly, 0.5 g of acryloyl chloride was added, and the mixture was reacted at room temperature for 4.5 h. The pH value was adjusted to 7, and the mixture was filtered, washed, and dried to obtain modified mesoporous silica.
[0020] Example 3 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1-1.1 g of epichlorohydrin, 1 g of potassium hydroxide, and 0.1 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, stirred at room temperature for 24 h, centrifuged, washed, and dried to obtain epoxidized mesoporous silica; S3: 10 g of epoxidized mesoporous silica and 100 mL of N,N-dimethylformamide were added to a reaction kettle and dispersed evenly, 3 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.02 g of hydroquinone were added, the temperature was controlled at 75°C, the reaction was kept warm for 6 h, 60°C deionized water was added to stop the reaction, the mixture was filtered, washed and dried to obtain component 1; S4: In a nitrogen atmosphere, 10 g of component 1, 5.6 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 1.2 g of sodium bicarbonate, 2.8 g of sodium dithionite, and 50 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 50°C, the reaction was kept warm for 9 hours, and then washed and dried to obtain component 2; S5: In a nitrogen atmosphere, 10 g of component 2, 2 g of lithium aluminum hydride, and 100 mL of tetrahydrofuran were added to a reaction kettle and dispersed evenly, and allowed to stand at room temperature for 9 h, and 10 mL of deionized water was added, and the mixture was filtered, washed, and dried to obtain component 3; S6: In a nitrogen atmosphere, 10 g of component three, 1.5 g of triethylamine, and 100 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly, 0.6 g of acryloyl chloride was added, and the mixture was reacted at room temperature for 6 h. The pH value was adjusted to 7, and the mixture was filtered, washed, and dried to obtain modified mesoporous silica.
[0021] Example 4 A method for preparing a modified resin material for ski helmet goggles comprises the following steps: A1: In a nitrogen atmosphere, 10 g of methyl methacrylate, 16 g of butyl methacrylate, 30 g of hydroxyethyl acrylate, 10 g of the modified mesoporous silica prepared in Example 1, 1.5 g of azobisisobutyronitrile, and 400 mL of methanol were added into a reaction kettle and dispersed evenly. The temperature was controlled at 60° C. and the reaction was kept warm for 24 h. Toluene was added to terminate the reaction and dried to obtain a silica-modified acrylate resin. A2: 60 g of silica-modified acrylic resin, 5 g of reactive diluent, 2 g of benzophenone, 3 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1 g of leveling agent BYK-306, and 60 g of ethanol were blended to obtain a modified resin material.
[0022] Example 5 A method for preparing a modified resin material for ski helmet goggles comprises the following steps: A1: In a nitrogen atmosphere, 10 g of methyl methacrylate, 16 g of butyl methacrylate, 30 g of hydroxyethyl acrylate, 10 g of the modified mesoporous silica prepared in Example 2, 1.5 g of azobisisobutyronitrile, and 400 mL of methanol were added into a reaction kettle and dispersed evenly. The temperature was controlled at 60° C. and the reaction was kept warm for 24 h. Toluene was added to terminate the reaction and dried to obtain a silica-modified acrylate resin. A2: 60 g of silica-modified acrylic resin, 5 g of reactive diluent, 2 g of benzophenone, 3 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1 g of leveling agent BYK-306, and 60 g of ethanol were blended to obtain a modified resin material.
[0023] Example 6 A method for preparing a modified resin material for ski helmet goggles comprises the following steps: A1: In a nitrogen atmosphere, 10 g of methyl methacrylate, 16 g of butyl methacrylate, 30 g of hydroxyethyl acrylate, 10 g of the modified mesoporous silica prepared in Example 3, 1.5 g of azobisisobutyronitrile, and 400 mL of methanol were added into a reaction kettle and dispersed evenly. The temperature was controlled at 60° C. and the reaction was kept warm for 24 h. Toluene was added to terminate the reaction and dried to obtain a silica-modified acrylate resin. A2: 60 g of silica-modified acrylic resin, 5 g of reactive diluent, 2 g of benzophenone, 3 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1 g of leveling agent BYK-306, and 60 g of ethanol were blended to obtain a modified resin material.
[0024] Comparative Example 1 The preparation method of modified mesoporous silica comprises the following steps: S1: 1 g of epichlorohydrin, 0.8 g of potassium hydroxide, and 0.08 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of nano-silicon dioxide was added, stirred at room temperature for 18 h, centrifuged, washed, and dried to obtain epoxidized silicon dioxide; S2: 10 g of epoxidized silica and 70 mL of N,N-dimethylformamide were added to a reaction kettle and dispersed evenly, 2.5 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.01 g of hydroquinone were added, the temperature was controlled at 70°C, the reaction was kept warm for 4.5 h, 55°C deionized water was added to stop the reaction, the reaction was filtered, washed and dried to obtain component 1; S3: In a nitrogen atmosphere, 10 g of component 1, 4.5 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 1 g of sodium bicarbonate, 2.5 g of sodium dithionite, and 40 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 45°C, the reaction was kept warm for 8 hours, and then washed and dried to obtain component 2; S4: In a nitrogen atmosphere, 10 g of component 2, 1.5 g of lithium aluminum hydride, and 70 mL of tetrahydrofuran were added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 8 h, 7 mL of deionized water was added, filtered, washed, and dried to obtain component 3; S5: In a nitrogen atmosphere, 10 g of component three, 1.2 g of triethylamine, and 70 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly. 0.5 g of acryloyl chloride was added and reacted at room temperature for 4.5 h. The pH value was adjusted to 7, and the modified silica was obtained by suction filtration, washing, and drying.
[0025] Comparative Example 2 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1 g of epichlorohydrin, 0.8 g of potassium hydroxide, and 0.08 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, stirred at room temperature for 18 h, centrifuged, washed, and dried to obtain epoxidized mesoporous silica; S3: 10 g of epoxidized mesoporous silica and 70 mL of N,N-dimethylformamide were added to a reaction kettle and dispersed evenly, 2.5 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.01 g of hydroquinone were added, the temperature was controlled at 70°C, the reaction was kept warm for 4.5 h, 55°C deionized water was added to stop the reaction, the reaction was filtered, washed and dried to obtain component 1; S4: In a nitrogen atmosphere, 10 g of component 1, 4.5 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 1 g of sodium bicarbonate, 2.5 g of sodium dithionite, and 40 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 45°C, the reaction was kept warm for 8 hours, and then washed and dried to obtain component 2; S5: In a nitrogen atmosphere, 10 g of component 2, 1.5 g of lithium aluminum hydride, and 70 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly. The mixture was allowed to stand at room temperature for 8 h, and 7 mL of deionized water was added. The mixture was filtered, washed, and dried to obtain modified mesoporous silica.
[0026] Comparative Example 3 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1 g of epichlorohydrin, 0.8 g of potassium hydroxide, and 0.08 g of tetrabutylammonium sulfate were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, stirred at room temperature for 18 h, centrifuged, washed, and dried to obtain epoxidized mesoporous silica; S3: Add 10g of epoxidized mesoporous silica and 70mL of N,N-dimethylformamide into a reactor and disperse them evenly. Add 2.5g of 2-acrylamido-2-methylpropanesulfonic acid and 0.01g of hydroquinone. Control the temperature at 70°C and keep the reaction for 4.5h. Add 55°C deionized water to stop the reaction. Filter, wash and dry to obtain modified mesoporous silica.
[0027] Comparative Example 4 The preparation method of modified mesoporous silica comprises the following steps: S1: Add 0.3 g of sodium hydroxide and 100 mL of deionized water into a reactor and disperse them evenly, add 1 g of hexadecyltrimethylammonium bromide, control the temperature at 60°C, add 5 mL of tetraethyl orthosilicate, keep the temperature for 4 h, filter, dry the solid, and calcine at 550°C for 4 h to obtain mesoporous silica; S2: 1 g of vinyl trimethoxysilane, 30 mL of anhydrous ethanol, and 30 mL of deionized water were added to a reaction kettle and dispersed evenly, 10 g of mesoporous silica was added, the temperature was controlled at 60°C, and the reaction was kept warm for 5 hours to obtain vinyl mesoporous silica; S3: In a nitrogen atmosphere, 10 g of vinyl mesoporous silica, 4.5 g of 1,1,2,2-tetrahydroperfluorohexyl iodide, 1 g of sodium bicarbonate, 2.5 g of sodium dithionite, and 40 mL of acetonitrile were added to a reaction kettle and dispersed evenly, deionized water was added, the temperature was raised to 45°C, the reaction was kept warm for 8 h, and then washed and dried to obtain component 2; S4: In a nitrogen atmosphere, 10 g of component 2, 1.5 g of lithium aluminum hydride, and 70 mL of tetrahydrofuran were added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 8 h, 7 mL of deionized water was added, filtered, washed, and dried to obtain component 3; S5: In a nitrogen atmosphere, 10 g of component three, 1.2 g of triethylamine, and 70 mL of tetrahydrofuran were added into a reaction kettle and dispersed evenly. 0.5 g of acryloyl chloride was added and reacted at room temperature for 4.5 h. The pH value was adjusted to 7, and the mixture was filtered, washed, and dried to obtain modified mesoporous silica.
[0028] Comparative Example 5 Compared with Example 5, Comparative Example 5 is only that the modified mesoporous silica prepared in Example 1 added in Example 5 is replaced by the modified silica prepared in Comparative Example 1 in an equal amount, and the other components and preparation method are completely the same as those in Example 5.
[0029] Comparative Example 6 Compared with Example 5, Comparative Example 6 is only replaced by an equal amount of modified mesoporous silica prepared in Example 1 added in Example 5 with modified mesoporous silica prepared in Comparative Example 2, and the other components and preparation method are completely the same as those in Example 5.
[0030] Comparative Example 7 Compared with Example 5, Comparative Example 7 is only that the modified mesoporous silica prepared in Example 1 added in Example 5 is replaced by the modified mesoporous silica prepared in Comparative Example 3 in an equal amount, and the other components and preparation method are completely the same as those in Example 5.
[0031] Comparative Example 8 Compared with Example 5, Comparative Example 8 is only that the modified mesoporous silica prepared in Example 1 added in Example 5 is replaced by the modified mesoporous silica prepared in Comparative Example 4 in equal amount, and the other components and preparation method are completely the same as those in Example 5.
[0032] Performance Testing Prepare the test sample: The modified resin materials prepared in Examples 4-6 and Comparative Examples 5-8 were applied as coatings on the surface of polycarbonate goggles, dried for 30 seconds, and irradiated with a high-pressure mercury arc lamp (300W / inch) at 1J / cm2 under nitrogen protection. 2 , coating thickness after curing is 5um; (1) Hardness: Tested according to GB / T 6739-1996 “Determination of paint film hardness by pencil method”. The test results are shown in Table 1. (2) Adhesion: Tested according to GB / T 9286-1998 “Scratch test for paint and varnish films”. The test results are shown in Table 1. (3) Friction resistance: The friction resistance tester was used for testing. The wear tester roller model was CS-10F, the wear load was 250g, and the wear tester speed was 80rad / min. The test results are shown in Table 1. Table 1: Statistical table of performance test data of Examples 4-6 and Comparative Examples 5-8
[0033] It can be seen from Table 1 that the modified resin material prepared in the present application is applied as a coating on the surface of the lens and has good friction resistance and adhesion properties.
[0034] (4) Anti-fog performance: The goggles coated with the modified resins prepared in Examples 4-6 and Comparative Examples 5-8 were placed in a 5°C environment, and 60°C hot water was placed at a distance of 5 cm from the goggles for fumigation for 15 seconds, and the anti-fog performance level was determined according to Table 2; the test results are shown in Table 3; Table 2: Anti-fog performance levels
[0035] (5) Water contact angle test: The test was carried out using a JC20000D5 contact angle meter at room temperature. 2.5uL of ultrapure water and hexadecane were dropped on the surface of the material respectively. The contact angles were measured to obtain the static hexadecane contact angle (OCA) and static water contact angle (WCA) of the surface, and the conversion parameter SP was calculated according to the following formula: Conversion parameters SP = OCA-WCA Wherein, OCA-hexadecane contact angle, °; WCA-decawater contact angle, °; the test results are shown in Table 3; (6) Light transmittance: Tested in accordance with GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”, using a color spectrum haze meter for measurement. The test results are shown in Table 3. (7) Water resistance: The goggles were immersed in boiling water and the time when the coating turned white and swollen was recorded every 5 minutes. The test results are shown in Table 3. Table 3: Statistical table of anti-fog performance test data of Examples 4-6 and Comparative Examples 5-8
[0036] As can be seen from Table 3, the modified resin material prepared in the present application as a coating gives the goggles good anti-fog performance and water resistance, and the conversion parameter SP is high, giving the goggles hydrophilic-oleophobic properties and a self-cleaning effect.
[0037] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a modified resin material for ski helmet goggles, characterized in that: The steps include: A1: In a nitrogen atmosphere, acrylate monomer, modified mesoporous silica, azobisisobutyronitrile and methanol are added to a reaction kettle and dispersed evenly. The temperature is controlled at 60-70°C, and the reaction is kept warm for 18-24 hours. Toluene is added to terminate the reaction and dried to obtain a silica-modified acrylate resin. A2: According to the raw material ratio, the silica-modified acrylic resin, the reactive diluent, the photoinitiator, the leveling agent and the solvent are blended to obtain a modified resin material; The preparation method of the modified mesoporous silica comprises the following steps: S1: Add epoxidized mesoporous silica and N,N-dimethylformamide into a reaction kettle and disperse them evenly, add 2-acrylamido-2-methylpropanesulfonic acid and hydroquinone, control the temperature at 65-75°C, keep the reaction for 3-6 hours, add 50-60°C deionized water to stop the reaction, filter, wash and dry to obtain component 1; S2: In a nitrogen atmosphere, component 1, 1,1,2,2-tetrahydroperfluorohexyl iodide, sodium bicarbonate, sodium dithionite, and acetonitrile are added to a reaction kettle and dispersed evenly, deionized water is added, the temperature is raised to 40-50°C, the temperature is kept for reaction for 6-9 hours, and then washed and dried to obtain component 2; S3: In a nitrogen atmosphere, component 2, lithium aluminum hydride and tetrahydrofuran are added to a reaction kettle and dispersed evenly, allowed to stand at room temperature for 6-9 hours, deionized water is added, filtered, washed and dried to obtain component 3; S4: In a nitrogen atmosphere, add triethylamine, tetrahydrofuran into a reaction kettle and disperse evenly, add acryloyl chloride, react at room temperature for 3-6 hours, adjust the pH value to 7-8, filter, wash and dry to obtain modified mesoporous silica.
2. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The acrylate monomer is obtained by mixing methyl methacrylate, butyl methacrylate and hydroxyethyl acrylate in a molar ratio of 1:1-2:2-3; the addition ratio of acrylate monomer, modified mesoporous silica, azobisisobutyronitrile and methanol in A1 is 50-80g: 5-15g: 1.5-2: 400-1000mL.
3. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The modified resin material in A2 includes the following raw materials in parts by weight: 50-80 parts of silica-modified acrylate resin, 5-10 parts of reactive diluent, 5-6 parts of photoinitiator, 0.1-2 parts of leveling agent, 1-2 parts of auxiliary agent, and 40-60 parts of solvent; The active diluent is one or more of acrylic acid, methacrylic acid, and hydroxyethyl methacrylate mixed in any ratio; The photoinitiator is a mixture of benzophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone in a mass ratio of 2:2-3; The leveling agent is any one of BYK-306, BYK-333, and BYK-3700; The solvent is any one of ethanol or isopropanol.
4. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The preparation method of epoxidized mesoporous silica comprises the following steps: adding epichlorohydrin, potassium hydroxide and tetrabutylammonium sulfate into a reaction kettle and dispersing them uniformly, adding mesoporous silica, stirring at room temperature for 12-24 hours, centrifuging, washing and drying to obtain epoxidized mesoporous silica.
5. The method for preparing a modified resin material for ski helmet goggles according to claim 4, characterized in that: The addition ratio of epichlorohydrin, potassium hydroxide, tetrabutylammonium sulfate and mesoporous silica is 1-1.1g: 0.6-1g: 0.05-0.1g: 10g.
6. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The addition ratio of epoxidized mesoporous silica, N,N-dimethylformamide, 2-acrylamido-2-methylpropanesulfonic acid, and hydroquinone in S1 is 10 g: 50-100 mL: 2-3 g: 0.01-0.02 g.
7. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The addition ratio of component 1, 1,1,2,2-tetrahydroperfluorohexyl iodide, sodium bicarbonate, sodium dithionite, acetonitrile, and deionized water in S2 is 10 g: 3.7-5.6 g: 0.8-1.2 g: 1.8-2.8 g: 50-100 mL: 25-50 mL.
8. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The addition ratio of component 2, lithium aluminum hydride, tetrahydrofuran, and deionized water in S3 is 10 g: 1-2 g: 50-100 mL: 5-10 mL.
9. The method for preparing a modified resin material for ski helmet goggles according to claim 1, characterized in that: The addition ratio of components tris, triethylamine, tetrahydrofuran, and acryloyl chloride in S4 is 10 g: 1-1.5 g: 50-100 mL: 0.3-0.6 g.
10. A modified resin material for ski helmet goggles, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-fog goggles nano coating and preparation method thereof
CN117924984A
Photocureable coating containing hydrophilic structure as well as preparation method and application of photocureable coating
CN118291033A
Radiation curable optical coating
WO2014016608A1